( x + 2xy ) * ( 2x - 1 )
x-y x^2-2xy+y^2 x+y
(x^3-2x^2y+y^2x+2x^2y-2xy^2)* ( 2x - 1 )
(x-y) (x^2-2xy+y^2 ) x+y
(x^3-2x^2y+y^2x+2x^2y-2xy^2) *(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
(x^3-xy^2) *(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
x(x^2-y^2)*(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
x((x-y)(x+y)))*(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
x*(2x - 1 )
(x^2-2xy+y^2 )
x*(2x - 1 )
(x-y)^2
подставляем
-2(-4-1) = 10
9 9
1)x=2 x=-1/3 x=1/3
2)y=-1 y=1
3)x=-1 x=2-√3 x=2+√3
4)x=-1 x=1
5)x=-1 x=1 x=-√2 x=√2
Объяснение:
1)9x³-18x²=x-2
9x²(x-2)-(x-2)=0
(x-2)(9x²-1)=0
(x-2)(3x-1)(3x+1)=0
x-2=0 3x-1=0 3x+1=0
x=2 x=1/3 x=-1/3
2)y³-y²=y-1
y²(y-1)-(y-1)=0
(y-1)(y²-1)=0
(y-1)(y-1)(y+1)=0
y=-1 y=1
3)x³-3x²-3x+1=0
(x³+1)-3x(x+1)=0
(x+1)(x²-x+1)-3x(x+1)=0
(x+1)(x²-x+1-3x)=0
(x+1)(x²-4x+1)=0
x+1=0 x²-4x+1=0
x=-1 D=16-4=12
x=(4-2√3)/2 = 2-√3 x=(4+2√3)/2 = 2+√3
4)x⁴-2x³+2x-1=0
(x⁴-1)-2x(x²-1)=0
(x²-1)(x²+1)-2x(x²-1)=0
(x²-1)(x²+1-2x)=0
x²-1=0 x²-2x+1=0
x=-1 x=1 (x-1)²=0
x=1
5)x⁴-3x²+2=0
x²=t
t²-3t+2=0
D=9-8=1>0
t₁+t₂=3 t₁t₂=2 t₁=1 t₂=2
x²=1 x=-1 x=1
x²=2 x=-√2 x=√2
-21х+29=-21*(-1/3)+29=36